ENTREPRENEURSHIP AND INNOVATION: OXFORDSHIRE'S HIGH-TECH ECONOMY - FIRM SURVIVAL, GROWTH AND INNOVATION - Helen Lawton Smith; Saverio Romeo (European Regional Science Association (ERSA), 2010)
This paper is about how entrepreneurial landscapes change over time through the survival, growth and innovative activities of high-tech firms. It explores how the Oxfordshire high-tech economy has evolved over time. It takes as its benchmark the 1980s, when the first study of Oxfordshire's high-tech economy was undertaken (Lawton Smith 1990). The literature of the 1980s, the period at which our analysis begins, was concerned with techno-economic changes (Freeman and Perez 1988) associated with the fifth Kondratieff wave, in which entrepreneurship was a key component. This view emphasized the reduced importance of scale economies, emergence of new industries with new organizational forms associated niches for small firms, and limited consolidation (Radosevic 2007). The paper will report on a follow-up to the first Oxfordshire study. It revisits the 182 companies identified as 'advanced technology' i.e. firms that undertake R&D in one or more of science, computer science and engineering. It will present a breakdown on survival and growth, by sector, by origin of firm e.g. university spin-offs, and by patent and licensing data as indicators of innovation and technological advance. It will thereby provide evidence on the size distribution of surviving firms (and where possible on ones that have ceased trading), markets that firms operate in (niche or mainstream) and the extent of consolidation through merger and acquisition. The study will therefore provide an understanding of processes of change, and where particular locations fit into broader systems of entrepreneurship and innovation.
Keywords: 330